2014
DOI: 10.1093/cvr/cvu174
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and highly efficient inducible cardiac gene knockout in adult mice using AAV-mediated expression of Cre recombinase

Abstract: AAV9-mediated expression of Cre is a promising approach for rapid and efficient conditional cardiac gene knockout in adult mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 43 publications
3
59
0
Order By: Relevance
“…Previous data indicated that combining AAV9 and a chicken minimal truncated TNNT2 promoter gave 4640-fold higher expression in the heart than in other organs in mice 37 . Here, we used a human minimal truncated TNNT2 promoter that showed restriction of FLAG-cMyBP-C protein expression to the heart 34 wks following systemic administration in vivo, supporting recent data using the same combination of AAV9 and TNNT2 promoter 13 wks after injection 38 . Serial echocardiographic analyses were done by a highly experienced investigator blinded to the genotype or treatment group.…”
Section: Discussionsupporting
confidence: 83%
“…Previous data indicated that combining AAV9 and a chicken minimal truncated TNNT2 promoter gave 4640-fold higher expression in the heart than in other organs in mice 37 . Here, we used a human minimal truncated TNNT2 promoter that showed restriction of FLAG-cMyBP-C protein expression to the heart 34 wks following systemic administration in vivo, supporting recent data using the same combination of AAV9 and TNNT2 promoter 13 wks after injection 38 . Serial echocardiographic analyses were done by a highly experienced investigator blinded to the genotype or treatment group.…”
Section: Discussionsupporting
confidence: 83%
“…Our AAV9-based approach (in which CTRP9 expression is driven by the cytomegalovirus-enhanced myosin light chain promoter) will lead to expression of CTRP9 in the whole heart, mainly in cardiomyocytes and in the liver. 31 This is different from the physiological situation where CTRP9 in the heart is mainly derived from endothelial cells (discussed in detail below) and where no expression in the liver is observed. However, given the technical difficulty to target endothelial cells by an AAV9 approach and in the light of the following facts that (1) CTRP9 is also expressed in cardiomyocytes (although at a much lower level), (2) it can act in these cells in an autocrine manner, and (3) in general, for a secreted factor, its net functional effects rather than its source might be more important, our approach still reveals important information at least as proof of concept.…”
Section: Discussionmentioning
confidence: 80%
“…Importantly, we were able to demonstrate effective pacing and defibrillation of mouse hearts by epicardial illumination even more than 1 year after the gene transfer. The great advantage of optogenetic defibrillation is that this would be, in contrast to electrical shocks, pain-free, because ChR2 expression would be restricted to cardiomyocytes by cardiomyocyte-specific AAV vector capsids (30) or promoters (31). Notably, AAV-mediated transduction will result in spatial heterogeneity of ChR2 expression, which is not expected to be pro-arrhythmic per se since ChR2 has neither a leak current in the absence of illumination nor does it affect the electrophysiological properties of cardiomyocytes (5).…”
Section: Discussionmentioning
confidence: 99%